2022
DOI: 10.3390/ijms23158798
|View full text |Cite
|
Sign up to set email alerts
|

PEBP4 Directs the Malignant Behavior of Hepatocellular Carcinoma Cells via Regulating mTORC1 and mTORC2

Abstract: Phosphatidylethanolamine binding protein 4 (PEBP4) is an understudied multifunctional small protein. Previous studies have shown that the expression of PEBP4 is increased in many cancer specimens, which correlates to cancer progression. The present study explored the mechanism by which PEBP4 regulates the growth and progression of hepatocellular carcinoma cells. Thus, we showed that knockdown of PEBP4 in MHCC97H cells, where its expression was relatively high, diminished activities of serine/threonine protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…In molecular pathways, we observed that 10 cancer Hallmark pathways including glycolysis, hypoxia, IL2-STAT5-signaling, ILl6-JAK-STAT5 signaling, MTORC1 signaling, notch signaling, peroxisome, reactive oxygen species pathway, spermatogenesis, and unfolded protein response were actively enriched in Cluster1 subtype. More intriguingly, these pathways are reported to be associated with malignant transformation [35][36][37]. For example, the previous findings in melanoma revealed that unfolded protein response is positively linked with tumor development, size, and patient prognosis [38,39].…”
Section: Discussionmentioning
confidence: 96%
“…In molecular pathways, we observed that 10 cancer Hallmark pathways including glycolysis, hypoxia, IL2-STAT5-signaling, ILl6-JAK-STAT5 signaling, MTORC1 signaling, notch signaling, peroxisome, reactive oxygen species pathway, spermatogenesis, and unfolded protein response were actively enriched in Cluster1 subtype. More intriguingly, these pathways are reported to be associated with malignant transformation [35][36][37]. For example, the previous findings in melanoma revealed that unfolded protein response is positively linked with tumor development, size, and patient prognosis [38,39].…”
Section: Discussionmentioning
confidence: 96%
“…Coincidentally, a few studies have demonstrated PEBP4 has a tightly connection with PI3K/AKT pathway. On the one hand, PEBP4 was confirmed to be as a scaffold protein for AKT and mTOR to enhance their interaction and to promote the activation of AKT and mTOR [ 16 ]. On the other hand, PEBP4 was found to positively regulate the phosphorylation of AKT in various cancer models [ 8 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, several recent research have revealed the relationship between PEBP4 and the PI3K/AKT pathway. PEBP4 is found to act as a scaffold protein for AKT/mammalian target of rapamycin (mTOR) signal transduction, and PEBP4 knock-down disturbs the interaction between AKT and mTOR [ 16 ]. In lung cancer cells, overexpression of PEBP4 promotes the AKT and mTOR phosphorylation, while PEBP4 knock-down shows the opposite result [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Aberrant expression of PEBP4 has been investigated in several types of cancers [27,28]. PEBP4 overexpression exacerbates the malignant behavior of hepatocellular carcinoma cells through the combined action of mTORC1 and mTORC2 [29]. In breast cancer, PEBP4 promotes cell migration and invasion by regulating the PI3K/AKT signaling pathway, whereas AKT downregulates calmodulin expression, contributes to the epithelial mesenchymal transition (EMT), and reduces intercellular adhesion [11].…”
Section: Discussionmentioning
confidence: 99%